2017
DOI: 10.1039/c7dt01272a
|View full text |Cite
|
Sign up to set email alerts
|

Stable AuIII complexes with four N-heterocyclic carbene groups can be prepared in high yield directly from KAuCl4

Abstract: Gold(iii) N-heterocyclic carbene (NHC) complexes of form [Au(NHC)Cl]Cl were synthesized by reaction of KAuCl with bis- and tetrakis(imidazolium) salts in the presence of a mild base. Treatment of these complexes with KPF afforded four-coordinate Au complexes of form [Au(NHC)](PF). X-Ray crystallography showed the [Au(NHC)] cations in the hexafluorophosphate salts to have a square planar Au(NHC) moiety [AuC 2.024(4)-2.082(7) Å]. In the [Au(NHC)Cl] cations in the chloride salts, coordination about Au was tetrago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…It is close to the chemical shifts of Au( iii )–C signals in similar Au( iii )-tetra(NHC) complexes, commonly observed between 147 and 145 ppm. 35 This might indicate a close relationship between the electronic structure of 1 and those relatively widespread compounds. 35 , 36 The backbone resonance at 123.2 ppm and the CH 2 bridges at 62.4 ppm are also very close to those of Au( iii )-tetra(NHC) complexes at about 124 and 63 ppm, respectively.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is close to the chemical shifts of Au( iii )–C signals in similar Au( iii )-tetra(NHC) complexes, commonly observed between 147 and 145 ppm. 35 This might indicate a close relationship between the electronic structure of 1 and those relatively widespread compounds. 35 , 36 The backbone resonance at 123.2 ppm and the CH 2 bridges at 62.4 ppm are also very close to those of Au( iii )-tetra(NHC) complexes at about 124 and 63 ppm, respectively.…”
Section: Resultsmentioning
confidence: 92%
“… 35 This might indicate a close relationship between the electronic structure of 1 and those relatively widespread compounds. 35 , 36 The backbone resonance at 123.2 ppm and the CH 2 bridges at 62.4 ppm are also very close to those of Au( iii )-tetra(NHC) complexes at about 124 and 63 ppm, respectively. The elemental analysis of isolated 1 is in excellent accordance with the calculated composition derived from SC-XRD.…”
Section: Resultsmentioning
confidence: 92%
“…The proton NMR studies have shown that the compound underwent H/D exchange reactions in D 2 O solution at 100 °C without decomposition (Scheme 46). [90] …”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…[89] In underwent H/D exchange reactions in D 2 O solution at 100°C without decomposition (Scheme 46). [90] Cucciolito et al prepared Au I À NHC complexes with a sugar moiety (198 and 199) by using sugar incorporated imidazolium precursor 196 as starting material. Treatment of imidazolium precursor 196 with the silver oxide in acetone produced the target Ag I À NHC complex 197.…”
Section: Goldà Nhc Complexesmentioning
confidence: 99%
“…Polyimidazolium linked macrocycles have also been utilized as precursors for N -heterocyclic carbene metal complexes and previously the Au(III) complex IV (Figure 2) was prepared the reaction of KAuCl 4 with a macrocyclic tetra -imidazolium salt II (Mageed et al, 2017). Additionally, dinuclear Au(II) and mixed valence Au(I)/Au(III) complexes of have been prepared by the oxidation of dinuclear Au(I) complexes of macrocyclic NHC ligands (Mageed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%